Gate voltage induced phase transition in magnetite nanowires - Gooth, Johannes; Zierold, Robert; Gluschke, Jan G.; Boehnert, Tim; Edinger, Stefan; Barth, Sven; Nielsch, Kornelius (Applied Physics Letters, 2013)
Since its discovery in 1939 the origin of the phase transition in magnetite (Fe3O4) has been an object of intensive research and great controversy. Here, electrical resistance measurements as a function of gate voltage have been performed on single-crystalline Fe3O 4 nanowires, showing that high electric fields trigger the breakdown of the insulating phase into a highly conductive state. Furthermore, the Verwey transition itself is suppressed by the gate voltage. © 2013 American Institute of Physics.
CRIS-Team Scopus Importer:2023-03-20